Mutation causing congenital myasthenia reveals acetylcholine receptor β/δ subunit interaction essential for assembly - Quiram, Polly A. (American Society for Clinical Investigation, 1999)
We describe a severe postsynaptic congenital myasthenic syndrome with marked endplate acetylcholine receptor (AChR) deficiency caused by 2 heteroallelic mutations in the β subunit gene. One mutation causes skipping of exon 8, truncating the β subunit before its M1 transmembrane domain, and abolishing surface expression of pentameric AChR. The other mutation, a 3-codon deletion (β426delEQE) in the long cytoplasmic loop between the M3 and M4 domains, curtails but does not abolish expression. By coexpressing β426delEQE with combinations of wild-type subunits in 293 HEK cells, we demonstrate that β426delEQE impairs AChR assembly by disrupting a specific interaction between β and δ subunits. Studies with related deletion and missense mutants indicate that secondary structure in this region of the β subunit is crucial for interaction with the δ subunit. The findings imply that the mutated residues are positioned at the interface between β and δ subunits and demonstrate contribution of this local region of the long cytoplasmic loop to AChR assembly. J. Clin. Invest. 104:1403–1410 (1999).